Engaging violence trauma, memory and representation (Cultural dynamics of social representation, 2014)
"This volume opens up new ground in the field of social representations research by focusing on contexts involving mass violence, rather than on relatively stable societies. Representations of violence are not only symbolic, but in the first place affective and bodily, especially when it comes to traumatic experiences. Exploring the responses of researchers, educators, students and practitioners to long-term engagement with this emotionally demanding material, the book considers how empathic knowledge can make working in this field more bearable and deepen our understanding of the Holocaust, genocide, war, and mass political violence. Bringing together international contributors from a range of disciplines including anthropology, clinical psychology, history, history of ideas, religious studies, social psychology, and sociology, the book explores how scholars, students, and professionals engaged with violence deal with the inevitable emotional stresses and vicarious trauma they experience. Each chapter draws on personal histories, and many suggest new theoretical and methodological concepts to investigate emotional reactions to this material. The insights gained through these reflections can function protectively, enabling those who work in this field to handle adverse situations more effectively, and can yield valuable knowledge about violence itself, allowing researchers, teachers, and professionals to better understand their materials and collocutors. Engaging Violence: Trauma, memory, and representation will be of key value to students, scholars, psychologists, humanitarian aid workers, UN personnel, policy makers, social workers, and others who are engaged, directly or indirectly, with mass political violence, war, or genocide"--